Climate Change Effects on Aquaculture Production: Sustainability Implications, Mitigation, and Adaptations - Maulu, Sahya; Hasimuna, Oliver J.; Haambiya, Lloyd H.; Monde, Concillia; Musuka, Confred G.; Makorwa, Timothy H.; Munganga, Brian P.; Phiri, Kanyembo J.; Nsekanabo, Jean DaMascene (Frontiers in Sustainable Food Systems, 2021)
Aquaculture continues to significantly expand its production, making it the fastest-growing food production sector globally. However, the sustainability of the sector is at stake due to the predicted effects of climate change that are not only a future but also a present reality. In this paper, we review the potential effects of climate change on aquaculture production and its implications on the sector’s sustainability. Various elements of a changing climate, such as rising temperatures, sea-level rise, disease, and harmful algal blooms, changes in rainfall patterns, the uncertainty of external inputs supplies, changes in sea surface salinity, and severe climatic events have been discussed. Furthermore, several adaptation options have been presented, and some of the gaps in existing knowledge as well as the areas that require further investigations have been highlighted. Overall, climate change effects and implications on aquaculture production sustainability are expected to be both negative and positive, the negative effects outweigh the positive ones. Adapting to the predicted changes in the short-term while taking mitigation measures in the long-term could be the only way towards sustaining the sector’s production. However, successful adaptation will depend on the adaptive capacity of the producers in different regions of the world.